Invasive Aspergillosis in Patients with Chronic Obstructive Pulmonary Diseases. Issue 4 (3rd June 2005) - Muquim, Aziz; Menzies, Dick; Dial, Sandra
Abstract : OBJECTIVES: To determine the outcomes, and clinical and therapeutic factors associated with the development of invasive pulmonary aspergillosis (IPA) in patients with obstructive pulmonary diseases. DESIGN: A case control study examining patients who developed IPA while hospitalized, and controls who were matched by year of hospitalization and type of obstructive lung disease. SETTING: A tertiary care university-affiliated respiratory hospital. PATIENTS: Twelve patients were identified who had developed nosocomial IPA. Each case was compared with four control patients: two with and two without Aspergillus colonization. RESULTS: Patients and control patients had similar demographic characteristics, comorbid illnesses and severity of underlying pulmonary disease. All cases required admission to the intensive care unit and eight patients (67%) died, whereas only 17% of control patients required admission to the intensive care unit and 7% died. The patients with IPA received significantly higher daily doses of corticosteroids (median 106 mg of prednisone or equivalent for 18 days) and more broad-spectrum antibiotics (median three antibiotics for 13 days) in hospital before the development of aspergillosis compared with the control patients (median 44 mg for 14 days, and 1.5 antibiotics for nine days, respectively). Among the control patients, those with Aspergillus colonization were more likely to have received corticosteroid therapy and broad-spectrum antibiotics during and in the month preceding the index hospitalization, although the hospital course was not different. CONCLUSIONS: IPA, although rare in patients with chronic obstructive lung diseases, was associated with high doses of corticosteroids and multiple broad-spectrum antibiotics. More judicious use of antibiotics and avoidance of prolonged high-dose corticosteroids may help prevent occurrences of IPA with its attendant serious morbidity and high mortality.